2020
DOI: 10.1080/19490976.2020.1799733
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate alterations of human colorectal cancer cells by 157 gut bacteria

Abstract: Several bacteria in the human gut microbiome have been associated with colorectal cancer (CRC) by high-throughput screens. In some cases, molecular mechanisms have been elucidated that drive tumorigenesis, including bacterial membrane proteins or secreted molecules that interact with the human cancer cells. For most gut bacteria, however, it remains unknown if they enhance or inhibit cancer cell growth. Here, we screened bacteria-free supernatants (secretomes) and inactivated cells of over 150 cultured bacteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 97 publications
2
17
0
1
Order By: Relevance
“…The fact that TX20005 CS alone stimulated host cell proliferation whereas CS from the mutant did not suggest that Sgg stimulation of host cell proliferation is mediated by Sgg T7SS T05 -secreted proteins. This is consistent with a recent study showing that CS from several Sgg strains were able to directly promote HT29 cell proliferation in the absence of bacteria [ 75 ]. At the moment, it is unclear whether the Sgg T7SS T05 -secreted factor mediating cell proliferation is the same as the one that enhances Sgg adherence to host cells.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that TX20005 CS alone stimulated host cell proliferation whereas CS from the mutant did not suggest that Sgg stimulation of host cell proliferation is mediated by Sgg T7SS T05 -secreted proteins. This is consistent with a recent study showing that CS from several Sgg strains were able to directly promote HT29 cell proliferation in the absence of bacteria [ 75 ]. At the moment, it is unclear whether the Sgg T7SS T05 -secreted factor mediating cell proliferation is the same as the one that enhances Sgg adherence to host cells.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our unpublished pilot in APC min mice at 6 weeks shows no increase in tumor burden in these susceptible mice upon S. gallolyticus UCN34 colonization. These strain level effects on cell proliferation for a multitude of CRC-associated bacteria were recently also shown by us for Fusobacterium nucleatum and Clostridium species (Taddese et al, 2020). These combined data suggest effective long-term colonization with S. gallolyticus only when tumors are present and, more importantly, that strain level differences are important for the observed effects.…”
Section: Discussionsupporting
confidence: 75%
“…pasteurianus strains 992 and NTB7. A phylogenetic tree of these S. bovis strains was published in Taddese et al, 2020 ( Taddese et al, 2020 ). Other bacterial strains were E. faecalis 19433 ( ), Enterobacter cloacae NTB9, Staphylococcus lugdunensis NTB8, Salmonella typhimurium NTB6, Escherichia coli Nissle 1917, and E. coli NTB5 ( Boleij et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human gastrointestinal tract is colonized by complex and diverse commensal microbial communities that contribute to the health of the host (Price et al, 2015;Garrett, 2019). The gut has approximately 40 trillion microbes, the vast majority of which are present in the large intestine (colon and rectum) (Sender et al, 2016;Wong and Yu, 2019;Taddese et al, 2020), and 60-80% of the microbes have not been identified due to culture-related difficulties (Van Citters and Lin, 2005;Shen et al, 2010). Therefore, the colon is the main contributor to the total number of bacteria in the digestive tract.…”
Section: Introductionmentioning
confidence: 99%